(untitled) (diségno, 2024)
In the context of the D’Annunzio pine forest, the spaces of the former Aurum liquor factory now the city museum ‘Factory of Ideas’, hosted the study day Dialoghi con gli Archivi di Architettura “Eredità contemporanee” (Dialogues with the Archives of Architecture “Contemporary Legacy”) organized by Caterina Palestini of the Department of Architecture of the Università degli Studi G. d’Annunzio Chieti-Pescara for the Unione Italiana per il Disegno in collaboration with the State Archives of Pescara. [read more]